Characterization of the temporal patterns of fish choruses in Poblacion, Liloan using the acoustic complexity index - Castañares, Ana Lorraine B. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Long-term monitoring of the coral reef in Poblacion, Liloan Cebu, is important in identifying key changes in the temporal soundscapes. Standardization of the Acoustic complexity index (ACI) was used in this study utilizing the 31.2 Hz frequency model by Dimoff et al. (2021). The index was used to characterize the temporal patterns, particularly lunar, monthly, and diel trends in the low-frequency range, using the data from December 2019 to March 2020 of the coral reef soundscapes in Liloan, Cebu. By assessing the temporal patterns, key changes in the coral reef can be determined, which may ultimately provide measures and ensure the preservation of the reefs. The ACI was calculated using the R soundecology package, and all the statistical analyses were done using R.4.1.2; On the other hand, quantifying fish calls were analyzed using Raven Pro 1.6. The results show inconsistency with the ACI and the long-term spectrogram (LTS) analysis. It was apparent in the long-term spectrogram that the soundscape during the new moon was louder than the soundscape on the full moon in December 2019. A comparison between lunar phases showed no significant difference in ACI between the new moon and the full moon in December 2019, but a significant difference was evident between the new moon in January 2020 and the full moon in March 2020. A comparison across months shows that there was a significant difference, with January and March having higher ACI. Lastly, diel patterns showed a similar pattern to the previous observations, but inconsistencies between the ACI and the number of fish calls were observed during sunrise and sunset. The study shows that despite the standardization efforts, ACI still does not offer reliable quantification of the quality of the soundscape.